Indonesia’s economic growth projections 2023-2025: empirical data analysis - Jasiyah, Rabiyatul; Raliby, Oesman; Hierdawati, Trie; Pamungkas, Binar Dwiyanto; Ningtyas, Septiana (SEAN Institute, 2024)
Projections for Indonesia's economic growth from 2023 to 2025 will be examined, with particular attention given to global concerns such as globalization and climate change. The report employs empirical data analysis to identify significant trends and sectors, while also addressing obstacles such as global uncertainty, sluggish digital change, and subpar infrastructure. The suggested approaches encompass economic diversification, investment in infrastructure, expedited digital transformation, legal restructuring, education, adaptable fiscal policy, and cooperation. It is anticipated that the execution of these policies will enhance economic growth, improve the well-being of individuals, and strengthen global competitiveness. This will be achieved through greater average income per person, decreased poverty rates, boosted exports, and improved investment opportunities. Ultimately, this study underscores the importance of adopting a comprehensive strategy to attain Indonesia's economic growth objectives for the period of 2023-2025, with the collaboration of the government, private sector, and society.